حركة الشيكانو ودورها في حركة الحقوق المدنية في الولايات المتحدة الأمريكية (Journal of Imam Al-Kadhim College, 2023)
After the end of the American-Mexican War in 1848, Mexican Americans people suffered from exclusion and marginalization due to the great disregard for the provisions of the Guadalupe Hidalgo treaty that was signed between the two parties in the same year, which called for the enjoyment of freedom, property, and religion for Mexican Americans people and their settlement in the western United States of America. But they were classified as second-class citizens by land registration laws and electoral laws that required knowledge of reading and writing in English as a qualification to vote, and as a school system dominated by white Americans, Mexican Americans people were forced to struggle to promote recognition of their cultural values and access to civil rights.    In the 1940s, Chicano was a derogatory name for the children of Mexican immigrants living in the United States. White Americans used it because they did not believe the Chicanos were native Americans, and people from Mexico used it because they did not believe the Chicanos were indigenous Mexicans . After several decades of mistreatment and naming, Mexican-Americans decided to adopt the term "Chicano" as a symbol of ethnic pride, and then the name was given to the Mexican-American civil rights movement that intensified in the 1960s.
Keywords: الكلمات المفتاحية : ( شيكانو- حقوق مدنية – أمريكيين مكسيكيين – منظمات)‏